Analysis of Budget Participation and Human Resource Competency and its Influence on Budget Absorption with Organizational Commitment as a Moderating Variable - Norawati, Suarni; Seprinaldi, Seprinaldi; Rahmawati, Rahmawati (Dinasti International Journal of Economics, Finance & Accounting, 2024)
Budget absorption is the process of implementing everything that has been planned and budgeted by a public organization in realizing community welfare. This research was conducted at the Riau Regional Police with the aim of testing and analyzing 1) the effect of budget participation on budget absorption; 2) the influence of human resource competency on budget absorption; 3) the role of organizational commitment moderating the relationship between budget participation and budget absorption and 4) the role of organizational commitment moderating the relationship between human resource competence and budget absorption. The population in this study were 55 Satker/Satwil in the Riau Regional Police. The sample used was a census technique, because the entire population was sampled, namely 55 Satker/Satwil with a total of 220 respondents. The data collection technique in this research is by using a questionnaire. This research uses the Partial Least Square (PLS) method by processing data and drawing conclusions using the SmartPLS version 3.0 program. The research results show that 1) budget participation influences budget absorption in the Riau Regional Police. 2) Human resource competency influences budget absorption at the Riau Regional Police. 3) Organizational commitment moderates the influence of budget participation on budget absorption in the Riau Regional Police. 4) Organizational commitment moderates the influence of HR competency on budget absorption in the Riau Regional Police